3D prostate surface detection from utrasound images - Shao, Fan (2008)
As a part of research on computer-assisted surgery, this thesis describes the research and development of a 3-dimensional prostate surface detection method for transrectal ultrasound (TRUS) images, aiming to achieve high validity (or accuracy), reliability (or consistency) and good speed (fast computation) of the algorithm.